Distributed System and Multimaster Replication Model on Reliability Optimation Database - Ravie Kurnia Laday; Heru Sukoco; Yani Nurhadryani (Institute of Advanced Engineering and Science, 2015)
Over the last two decades, significant advances have been made in the development of techniques for evaluating the performance, availability, and reliability of computer and communication systems in integration [11]. The reliability of the network is an important parameter in network [4]. Reliability is the performance, availability and security is a factors most important in a network . A distributed system is a system architecture in which computers can communicate and share resources [8]. This research applies a distributed system with load balancing and multimaster replication techniques in database. The results of this study found that the design of a system built to keep the data for connections between servers is in good condition and occurs down on one of the database server.DOI: http://dx.doi.org/10.11591/telkomnika.v13i3.7114